The treatment of femoral shaft fractures in adults with hybrid Ilizarov external fixator - Belhan, Oktay; Ekinci, Ahmet; Karakurt, Lokman; Yilmaz, Erhan; Serin, Erhan (Turkish Joint Diseases Foundation, 2008)
Objectives The aim of this study was to evaluate the results of femoral shaft fractures treated with hybrid Ilizarov external fixator. Patients and methods Patients with femoral fractures (n=30) treated by hybrid Ilizarov external fixator were evaluated. There were 8 (26.7%) females and 22 (73.3%) males and the mean age was 34.6 (18-56) years. There were 25 open fractures. According to Gustillo-Anderson classification; 9 were Grade 11, 7 were Grade III A and 9 were Grade III B. In all cases, while two rings were placed distal to the fracture line using connectors and different numbers of 90 degrees-120 degrees, femoral arches, these rings were fixed to the proximal segment by using the half pins. Results All patients were evaluated in accordance with functional and radiographic results; 43.3% were excellent, 33.3% good, 16.6% intermediate and 6.6% poor. Conclusion Applying a standart frame configuration may not be possible in proximal femur fractures due to the complex anatomical structure and rich neurovascular configuration. While using K-wires, there will be a risk of introducing K-wires to crucial neurovascular areas, so hybrid external fixators are preferred. We choose hybrid fixators for their safety and ease of application for femural shaft fractures.
Keywords: femur shaft fractures; external fixator; hybrid Ilizarov fixator